Early Ideas in Underground Coal Gasification and Their Evolution - Alexander Y. Klimenko (Energies, 2009)
This article follows the development of early UCG (underground coal gasification) ideas. Historical facts are discussed mainly from the technological perspective and early experiments in UCG are analyzed. Our search for the first successful UCG experiment brings to light a new finding, which was commonly overlooked in previous reviews. We also outline the key role that engineer and inventor A. G. Betts played in introducing technologies utilizing unmined coal; his original ideas are visible in the first successful UCG experiments and in modern UCG technology.